7.0k views
7 votes
3х - у = -3
х+у= -1 using elimination
method​

User Inser
by
5.3k points

2 Answers

8 votes

Answer:

x = -1

y = 0

Explanation:

3x - y = -3 -------------------(I)

x + y = -1 ------------------(II)

Add equation (I) & (II). Now, y will be eliminated and you can find the value of x

(I) 3x - y = -3

(I) x + y = -1

4x = -4

x = -4/4

x = -1

Plugin x = -1 in equation (II)

-1 + y = -1

y = -1 +1

y = 0

User Sijan Gurung
by
6.2k points
7 votes

Answer:

Your solution is (-1, 0)

Explanation:

3x - y = -3

x + y = -1

The elimination method eliminates one variable at a time to find the other variable.

Here we can see that the y variable will naturally be eliminated.

3x - y = -3

x + y = -1

--------------

4x = -4

Divide both sides by 4 to isolate x.

x = -1

Now plug this value back into one of the equations.

3(-1) - y = -3

Multiply.

-3 - y = -3

Add 3 to both sides.

-y = 0

Divide both sides by -1.

y = 0

Your solution is (-1, 0)

Check this solution by plugging these values into the second equation.

-1 + 0 = -1

-1 = -1

Your solution is correct.

Hope this helps!

User Tsagana Nokhaeva
by
4.9k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.